2016
DOI: 10.4103/0971-6203.181635
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the dose distribution effect related with collimator angle in volumetric arc therapy of prostate cancer

Abstract: To investigate the dose-volume variations of planning target volume (PTV) and organ at risks (OARs) in eleven prostate cancer patients planned with single and double arc volumetric modulated arc therapy (VMAT) when varying collimator angle. Single and double arc VMAT treatment plans were created using Monaco5.0® with collimator angle set to 0°. All plans were normalized 7600 cGy dose to the 95% of clinical target volume (CTV) volume. The single arc VMAT plans were reoptimized with different collimator angles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…He concluded that a higher D 95 (PTV) was found for single arc VMAT with 15°collimator angle. Lower rectum doses obtained for 75-285°collimator angles [28]. In our study, through changing the angle of the collimator from 0 to 90°with IMRT, it could reduce the maximum point dose of ipsilateral lens.…”
Section: Lomax Et Al Compared Intensity Modulation Inmentioning
confidence: 48%
“…He concluded that a higher D 95 (PTV) was found for single arc VMAT with 15°collimator angle. Lower rectum doses obtained for 75-285°collimator angles [28]. In our study, through changing the angle of the collimator from 0 to 90°with IMRT, it could reduce the maximum point dose of ipsilateral lens.…”
Section: Lomax Et Al Compared Intensity Modulation Inmentioning
confidence: 48%
“…We determined the collimator angle based on 2‐D beam's eye view images; in further studies, it might be useful to obtain the collimator angle in 3‐D directions according to the shape of the target, because it might be better to irradiate the target area and protect the OAR. Conventionally, volumetric modulated arc therapy (VMAT) plans generally only use one fixed collimator angle; however, the quality of VMAT plans are also related to the collimator angles 32–42 . More recently, dynamic collimator optimization has been proven to have a positive influence on dosimetric distribution in VMAT 43–47 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, volumetric modulated arc therapy (VMAT) plans generally only use one fixed collimator angle; however, the quality of VMAT plans are also related to the collimator angles. [32][33][34][35][36][37][38][39][40][41][42] More recently, dynamic collimator optimization has been proven to have a positive influence on dosimetric distribution in VMAT. [43][44][45][46][47] Similarly, acquiring multiple collimator angles during gantry rotation using the CLx technique in VMAT plans also warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that dose coverage and dose-volume histogram (DVH) statistics were related to collimator angle selections in VMAT. [26][27][28][29] However, in clinics, collimator parameters are commonly set by a template with default values following institutional guidelines and conventions. One common practice is employing dual arcs with symmetric collimator angles (eg, 30 and 330 ) and full rotations.…”
Section: Introductionmentioning
confidence: 99%